Fate of non O157 Shigatoxigenic Escherichia coli in ovine manurecomposting - Marin, J. M. (2014)
Livestock manure may contain pathogenic microorganisms which pose a risk to thehealth of animal or humans if the manure is not adequately treated or disposed of. Todetermine the fate of Shiga toxigenic Escherichia coli (STEC) nonO157 in composted manure from naturally colonized sheep, fresh manure was obtainedfrom animals carrying bacterial cells with stx1/ stx2 genes. Two composting systems were used, aerated andnon-aerated, and the experiments were done in Dracena city, São Paulo State. Everyweek, for seven weeks, one manure sample from six different points in both systemwas collected and cultured to determine the presence of E. coli, thepresence of the virulence genes in the cells, and also the susceptibility to 10antimicrobial drugs. The temperature was verified at each sampling. STEC non-O157survived for 49 days in both composting systems. E. coli non-STECshowing a high degree of antibiotic resistance was recovered all long the compostingperiod. No relationship was established between the presence of virulence genes andantibiotic resistance. The presence of virulence genes and multiple antibioticresistances in E. coli implicates a potential risk for these genespread in the human food chain, which is a reason for concern.